Translation and translanguaging - Baynham, Mike 1950-; Lee, Tong-King (Routledge, 2019)
Translation and Translanguaging brings into dialogue translanguaging as a theoretical lens and translation as an applied practice. This book is the first to ask: what can translanguaging tell us about translation and what can translation tell us about translanguaging? Translanguaging originated as a term to characterize bilingual and multilingual repertoires. This book extends the linguistic focus to consider translanguaging and translation in tandem - across languages, language varieties, registers, and discourses, and in a diverse range of contexts: everyday multilingual settings involving community interpreting and cultural brokering, embodied interaction in sports, text-based commodities, and multimodal experimental poetics. Characterizing translanguaging as the deployment of a spectrum of semiotic resources, the book illustrates how perspectives from translation can enrich our understanding of translanguaging, and how translanguaging, with its notions of repertoire and the "moment", can contribute to a practice-based account of translation. Illustrated with examples from a range of languages, including Spanish, Chinese, Japanese, Czech, Lingala, and varieties of English, this timely book will be essential reading for researchers and graduate students in sociolinguistics, translation studies, multimodal studies, applied linguistics, and related areas
Keywords: Translating and interpreting; Translanguaging (Linguistics)